2006
DOI: 10.1242/jcs.03160
|View full text |Cite
|
Sign up to set email alerts
|

ER stress-induced apoptosis and caspase-12 activation occurs downstream of mitochondrial apoptosis involving Apaf-1

Abstract: Accumulation of unfolded proteins induces endoplasmic reticulum (ER) stress. Excessive and prolonged stresses lead cells to apoptosis. However, the precise molecular mechanisms of ER stress-induced apoptosis have not been fully elucidated. We investigated the involvement of the apoptosome in ER stress-induced cell death pathway using mouse embryonic fibroblasts (MEFs) and mice deficient for Apaf-1. Apaf-1-deficient MEFs showed more resistance to ER stress-inducing reagents as compared with wild type cells. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(131 citation statements)
references
References 50 publications
9
121
0
1
Order By: Relevance
“…14 Additionally, we find that a zVAD-fmk inhibitable caspase, such as caspase 12, 9 does not act upstream of the mitochondrial release of cytochrome c during ER stressinduced apoptosis, as addition of zVAD-fmk did not block cytochrome c release in response to TU treatment (Figure 5a). In agreement with this finding, recent studies have indicated that caspase 12 is a downstream target of caspases 3 38 and that caspase 12 and human caspase 4 are dispensable for ER stress-induced apoptosis. 39 Therefore, caspase 12 is not likely to play an essential role as a link between the ER and mitochondrial to release cytochrome c in sympathetic neurons.…”
Section: Discussionsupporting
confidence: 74%
“…14 Additionally, we find that a zVAD-fmk inhibitable caspase, such as caspase 12, 9 does not act upstream of the mitochondrial release of cytochrome c during ER stressinduced apoptosis, as addition of zVAD-fmk did not block cytochrome c release in response to TU treatment (Figure 5a). In agreement with this finding, recent studies have indicated that caspase 12 is a downstream target of caspases 3 38 and that caspase 12 and human caspase 4 are dispensable for ER stress-induced apoptosis. 39 Therefore, caspase 12 is not likely to play an essential role as a link between the ER and mitochondrial to release cytochrome c in sympathetic neurons.…”
Section: Discussionsupporting
confidence: 74%
“…Overexpression of Gadd153 resulted in the downregulation of Bcl-2 expression, depletion of glutathione levels and exaggerated production of reactive oxygen species, leading to sensitization of cells to endoplasmic reticulum (ER)-stress induced apoptosis [34]. In mouse embryonic fibroblasts, ER-stressinduced apoptosis and activation of caspase-12 is shown to occur downstream of mitochondrial apoptosis involving Apaf-1 [35].…”
Section: Discussionmentioning
confidence: 99%
“…The ER is associated with the synthesis, initial post-translational modification, folding and maturation of proteins and is a major regulator of intracellular Ca 2 þ homeostasis (Shiraishi et al, 2006). Improper protein maturation, unfavourable environmental conditions, protein redox and glycosylation status alterations or nutrient and ATP deprivation, disrupt ER function inducing ER stress and the unfolded protein response (UPR).…”
Section: Bi-1 Modulation Of Er Stress-induced Apoptosismentioning
confidence: 99%
“…ER stress signalling is mediated by three transmembrane proteins ATF6 (activating transcription factor 6), PERK (PKR-like ER kinase) and IRE1 (inositolrequiring-1), which are kept inactive through interaction (Imaizumi et al, 2001;Shiraishi et al, 2006). Initially, adaptation to ER stress induces cleavage of ATF6 releasing its cytosolic fraction, which translocates to the nucleus inducing the expression of ER chaperones and the ER associated degradation machinery (ERAD) genes.…”
Section: Bi-1 Modulation Of Er Stress-induced Apoptosismentioning
confidence: 99%
See 1 more Smart Citation